PARAMETRIC STUDY FACTORS AFFECTING PROJECT MANAGEMANT OF CONSTRUCTION IN SOUTH LIBYA - Mohamed, Alsadik; Astuti, Winny; Rahmadi, Agus Parwito (Jurnal Teknik Sipil, 2014)
Abstract Unexpected delays in construction projects are caused by owner,contractor, or a third party in which several types of delays may occurconcurrently. The effect of delays does not only influence the construction industry but the overall economy as well. As such, the objectives of the presented research in this paper are to identify, study, the factors that caused the delay in project duration. Simulation-based Analytic Hierarchy Process (AHP). Were collected the data from owner and companies in Ghat, Libya. The model is implemented to the collected data, which show robust results. Based upon collected the data for the project of 3000 Houses in Ghat. The priorities according to the analysis of hierarchical (AHP) are from the questioners, the most important in this problem of project is Management conditions ranked first at 0.470. The next is Project conditions ranked 0.370 the last Environmental conditions ranked at 0.160.This result is to the real case study of project. In management the result problem, payment delay and Time to make Decision and productivity uncertainty of labor is big problem from management condition. The Project conditions are the second problem from the project. In project conditions the result problem, material availability is biggest problem from project condition. The environmental condition is the third problem from the project. In environmental conditions the result problem, labor strike and shortage of human resources is largest problem from environmental conditions. Keywords: Factors, Delays, construction, AHP, Libya.